Coevolution of life history traits and morphology in female subterranean amphipods. Issue 5 (11th September 2012) - Fišer, Cene; Zagmajster, Maja; Zakšek, Valerija
<x xml:space="preserve">Abstract</x> Subterranean species show a distinct morphology, yet the adaptive significance of some traits, like body size and shape, is poorly understood and cannot be explained solely by distinct environmental conditions (darkness, less food). We predicted that in females some morphological changes may have co‐evolved with life history traits, and that co‐evolving life history traits provide at least part of the explanation for evolutionary changes of morphology. Using museum material we tested this prediction on the subterranean amphipod genus Niphargus. We studied six species found in springs and eight species found in cave lakes. We treated them as two ecologically distinct groups, and the major ecological differences between them were the availability of nutrients and the water currents. Cave species were found to be larger and stouter (as inferred from the shape of coxal plates, which are part of the marsupium), they had larger eggs and lower reproductive effort per brood, whereas the egg number and brood volume if corrected for the body size were not different. Using phylogenetic independent contrasts, we found a positive correlation between body shape and egg volume, a positive correlation between body size and egg volume, and a negative correlation between body size and reproductive effort per brood. We tentatively conclude that evolutions of morphology and life histories are functionally connected and that co‐evolving traits contribute to overall selective regime.